2011
DOI: 10.1007/s12022-011-9160-0
|View full text |Cite
|
Sign up to set email alerts
|

Classical and Follicular Variant Papillary Thyroid Carcinoma: Comparison of Clinical, Ultrasonographical, Cytological, and Histopathological Features in 444 Patients

Abstract: Follicular variant papillary thyroid carcinoma (FVPTC) is the most common variant of papillary thyroid carcinoma (PTC) after classical PTC (CPTC). In this study, we aimed to compare functional status, ultrasonographical features, cytological results, and histopathological characteristics of patients with CPTC and FVPTC. Preoperative thyroid functions, thyroid autoantibodies, ultrasonographical features, cytology, and histopathology results of 354 (79.9%) CPTC and 90 (20.3%) FVPTC patients were reviewed retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
44
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 34 publications
11
44
1
1
Order By: Relevance
“…The mean tumor size of patients with FV-PTC was larger than that of the patients with C-PTC, which is in agreement with the results of studies by Chang et al (10), Ozdemir et al (17), Burningham et al (19), Jain et al (49) and Kim et al (50). Ozdemir et al (17) and Kim et al (50) also reported that compared to C-PTC, FV-PTC has more benign sonographic features, a lower incidence of a sonographically malignant grade and a lower diagnostic rate of PTC on fine-needle aspiration biopsy (FNAB). Thus, the lower rate of suspicious findings in FV-PTC lesions may have caused evaluation of larger FV-PTC lesions by FNAB, resulting in the detection of these lesions at a later stage.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The mean tumor size of patients with FV-PTC was larger than that of the patients with C-PTC, which is in agreement with the results of studies by Chang et al (10), Ozdemir et al (17), Burningham et al (19), Jain et al (49) and Kim et al (50). Ozdemir et al (17) and Kim et al (50) also reported that compared to C-PTC, FV-PTC has more benign sonographic features, a lower incidence of a sonographically malignant grade and a lower diagnostic rate of PTC on fine-needle aspiration biopsy (FNAB). Thus, the lower rate of suspicious findings in FV-PTC lesions may have caused evaluation of larger FV-PTC lesions by FNAB, resulting in the detection of these lesions at a later stage.…”
Section: Discussionsupporting
confidence: 91%
“…Passler et al (12) suggested that there was a significantly higher prevalence of multifocality in patients with FV-PTC compared to patients with C-PTC, but the opposite was reported by Gao et al (31) and Trovisco et al (47). Certain studies reported a higher prevalence of capsular invasion and vascular invasion in the FV-PTC (10,20,51), whereas others did not (17,43,47). Although the majority of the C-PTCs do not have a tumor capsule, patients with C-PTC (28.1%) and patients with FV-PTC (30.2%) showed a similar high prevalence of capsular invasion of tumor in the present meta-analysis.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Even focal nuclear features of papillary carcinoma thyroid in fine needle aspiration cytology are strongly associated with papillary carcinoma at resection, [12] particularly FVPTC [13]. Higher tumor size and rate of suspicious for malignancy cytology were significantly higher in FVPTC [14]. If we use histologic diagnosis as the gold standard, the sensitivity and specificity of FNAC diagnosis of FVPTC were 42% and 83%, respectively [15].…”
Section: Discussionmentioning
confidence: 99%